Table S5 from A Single-Cell Taxonomy Predicts Inflammatory Niche Remodeling to Drive Tissue Failure and Outcome in Human AML - Lanpeng Chen (16918293) (2025)
Table S5 Differentially expressed genes in residual normal/pre-leukemic HSCs in AML vs. HSCs from NBM (scRNAseq)